Prototype and Implementation of Website Content Translation of Desa Karyawangi - Ida Zuraida Supri; Heri Heryono; Atri Nadia Astarina; Hendar Hendar; Meita L L Sujatna (Universitas Cokroaminoto Palopo, 2022)
Community Service or Pengabdian kepada masyarakat (PkM) is one of the Tri Dharma of Higher Education (teaching, research, and community service) must be fulfilled by lecturers. Contributing to the surrounding community is one of the forms of responsibility that should be carried out. This Community Service program is the follow- up of the previous one. English Department of the Faculty of Humanities Widyatama University has developed a village website, given training to students and teachers for making and writing website content for Desa Karyawangi as the partner of this community service last year. The second batch of this community service is maintaining web content and adding translation features to the website so that people from different language users are able to gain information displayed in the website. Desa Karyawagi, located in Kecamatan Parongpong Kabupaten Bandung Barat is the partner of this community service. Lack of knowledge and skill of using digital media and English mastery are the problems Desa Karyawangi has. Therefore, it is urgent to give them assistance in promoting tourism and disseminating information. This research employs descriptive qualitative research. Data collection is done by distributing online questionnaires, conducting interviews towards user’s experience. This community service has enabled the community of Desa Karyawangi to be more aware of the importance of being technology savvy. The results of the research show that 1) the villagers are aware of the importance of using websites for spreading and gaining information and 2) Translation features added to the website gives a positive effect to the tourism and economy aspects.